Analysis of the Parameters Affecting the Surface Sanding of Pinus elliottii and Corymbia citriodora Wood Species - Leite, Sueli Souza [UNESP]; Kim Jesus, Gessica Mina [UNESP]; Sampaio Alves, Manoel Cleber de [UNESP]; Valarelli, Ivaldo de Domenico [UNESP]; Pereira Bueno, Marcus Antonio [UNESP]; Rossetto Dinhane Magorbo, Fernando Christiane [UNESP]; Moizes, Fabio Alexandre [UNESP]; Salvadeo, Vitor Manoel [UNESP] (North Carolina State Univ Dept Wood & Paper Sci, 2019)
Wood is a versatile and renewable material. It features characteristic mechanical resistance, thermal and electrical insulation, easy workability, and low energy consumption during processing. These properties make it attractive compared with other materials, mainly in the manufacturing and civil construction industries. One of the most important processes in the logging industry is sanding, though it is treated empirically by companies without a systematic study of the influence of its parameters, and it incurs high costs in this sector. Therefore, this work analyzed the effects of the sandpaper parameters (grit size and type of abrasive), wood parameters (species and fiber direction), and contribution percentage thereof on the behavior of the surface roughness and removal rate of the material. The Taguchi method was applied, and tests were performed on a flat sander with a pneumatic circuit and monitoring system for data acquisition. The tests were analyzed statistically by analysis of variance. The results showed that the surface roughness and removal rate were significantly influenced by the sandpaper parameters, but not by the wood parameters. Also, the aluminum oxide sandpaper presented greater durability and resulted in lower roughness values.
Keywords: Surface quality; Roughness; Removal rate; Pinus elliottii; Corymbia citriodora